2013
DOI: 10.1007/s10393-013-0833-7
|View full text |Cite
|
Sign up to set email alerts
|

Fitness Consequences of Infection by Batrachochytrium dendrobatidis in Northern Leopard Frogs (Lithobates pipiens)

Abstract: The amphibian chytrid fungus, Batrachochytrium dendrobatidis (Bd), has been linked to amphibian declines and extinctions worldwide. The pathogen has been found on amphibians throughout eastern North America, but has not been associated with mass die-offs in this region. In this study, we conducted laboratory experiments on the effects of Bd infection in a putative carrier species, Lithobates pipiens, using two estimators of fitness: jumping performance and testes morphology. Over the 8-week study period, peak … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
40
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 56 publications
2
40
3
Order By: Relevance
“…Because L. rheocola has not coexisted with B. dendrobatidis for an extended period, it is likely that the pattern we observed reflects a generalized, plastic response to a pathogenic infection, in which infected frogs increase their present reproductive effort at the expense of possible future reproductive effort. A functionally similar response to infection by B. dendrobatidis occurs in northern leopard frogs (Lithobates pipiens); the testes of infected males are larger and contain more sperm than those of uninfected males [15]. Studies on other taxa reveal that present reproductive effort can increase as life expectancy decreases [10][11][12][13][14][15][16][17][18].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Because L. rheocola has not coexisted with B. dendrobatidis for an extended period, it is likely that the pattern we observed reflects a generalized, plastic response to a pathogenic infection, in which infected frogs increase their present reproductive effort at the expense of possible future reproductive effort. A functionally similar response to infection by B. dendrobatidis occurs in northern leopard frogs (Lithobates pipiens); the testes of infected males are larger and contain more sperm than those of uninfected males [15]. Studies on other taxa reveal that present reproductive effort can increase as life expectancy decreases [10][11][12][13][14][15][16][17][18].…”
Section: Discussionmentioning
confidence: 93%
“…Frogs infected by B. dendrobatidis often have lower body condition than uninfected frogs [28][29][30]; when this occurs, they might reduce calling effort. On the other hand, infected hosts with relatively good body condition may have the plasticity to respond to the infection by investing more in present reproductive effort than uninfected individuals when their expectation of survival to the next reproductive bout is lower [13][14][15][16][17][18]. Such a response could at least partially counteract the effects of natural selection on disease resistance, because it may reduce differences in reproductive success between more and less vulnerable males.…”
Section: Introductionmentioning
confidence: 99%
“…In such circumstances, infected frogs might be selected to increase calling effort at the expense of growth, survival or other life-history traits to ensure reproductive success [17]. Indeed, previous studies have demonstrated that testes of Bd-infected frogs are larger and contain more sperm than those of uninfected controls [18]. Furthermore, Bd-infected males, when in good condition, are more likely than uninfected males to be callers [19].…”
Section: Discussionmentioning
confidence: 99%
“…We examine the influence of two parasites that have distinct life-history strategies: an ectoparasitic tick (Carios sp., possibly an undescribed taxon) and a fungal skin pathogen Batrachochytrium dendrobatidis (Bd). Infection with Bd inhibits host immune responses (Fites et al 2013), produces changes in advertisement calls (An and Waldman 2016), impacts growth (Burrowes et al 2008b), and limits movement (Chatfield et al 2013). Tick parasitism causes skin ulceration, inflammation, desiccation, blood loss, and anemia (Lehmann 1993, Goldberg et al 1996, all of which could affect the visual display of yellow coloration as well as overall health condition of hosts.…”
Section: Introductionmentioning
confidence: 99%
“…Tick parasitism causes skin ulceration, inflammation, desiccation, blood loss, and anemia (Lehmann 1993, Goldberg et al 1996, all of which could affect the visual display of yellow coloration as well as overall health condition of hosts. Infection with Bd inhibits host immune responses (Fites et al 2013), produces changes in advertisement calls (An and Waldman 2016), impacts growth (Burrowes et al 2008b), and limits movement (Chatfield et al 2013). Infection by both pathogens should be higher at breeding sites.…”
Section: Introductionmentioning
confidence: 99%